Comparative bioassay methods to determine diamide susceptibility for two coffee pests. (July 2019) - Gonring, Alfredo Henrique Rocha; Silva, Fábio Maximiano de Andrade; Picelli, Eduardo da cruz Maduro; Plata-Rueda, Rosa Angelica; Gorri, Jéssica Emiliane Rodrigues; Fernandes, Flávio Lemes
Abstract: Hypothenemus hampei Ferrari (Coleoptera: Curculionidae: Scolytinae) and Leucoptera coffeella Guérin-Méneville (Lepidoptera: Lyonetiidae) are major pests of coffee. Diamides, are a new group of insecticides that activate ryanodine receptors causing muscle contraction, and have been used to control H. hampei and L. coffeella . Bioassay methods need to be standardized for insecticide susceptibility studies on H. hampei with cyantraniliprole and L. coffeella with chlorantraniliprole. Four bioassay methods for H. hampei (topical application with a microsyringe, artificial diet, immersion of green coffee fruits in insecticide solution, and coffee branch bagging) and five for L. coffeella (spraying coffee seedlings, immersion of coffee leaves, immersion of filter paper and topical application with microsyringe were evaluated. The best performing method was selected based on the greater slope (β) of the probit curve, lower LC50, lower natural mortality in the control, and lower variance. The results showed that the best methods for bioassays were the artificial diet for H. hampei and spraying of coffee seedlings for L. coffeella . Graphical abstract: Image 1 Highlights: Diamides are efficient to control of Leucoptera coffeella and Hypothenemus hampei . Bioassay of mortality with diamides is not real to pests of the coffee. Artificial diet is a good method to coffee berry borer. Spray of coffee seedlings is a good method to leafminer.